Magnetic and transport properties driven by lattice strain in La0.7Ca0.3MnO3/BaTiO3 and La0.7Sr0.3MnO3/BaTiO3 bilayered films - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Yu, K.K.; Jun, S.J.; Park, S.Y.; Park, J.S.; Lee, Y.P.; Svetchnikov, V.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The microstructure and the magnetic and transport properties of La0.7Ca0.3MnO3 andLa0.7Sr0.3MnO3 films deposited on a BaTiO3 layer (LCMO/BTO and LSMO/BTO) and on a LaAlO3 (001) single crystal (LCMO/LAO and LSMO/LAO) by rf-magnetron sputtering using «soft» (or powder) targets are investigated. The films grown on BTO demonstrate biaxial tensile in-plane and compressive out-of-plane strains, while the films grown on LAO, in contrast, manifestcompressive in-plane and tensile out-of-plane strains. The films with biaxial tensile in-plane lattice strain undergo the magnetic transition at a higher temperature than that for the biaxial compressive case. This argues that the Mn–O–Mn bond-angle variation, controlled by the lattice strain, plays a more important role in the formation of the spin ordering than the attendant modification of the Mn–O bond length. It was shown that the magnetic inhomogeneity, expressed by a significant difference between the field-cooled and zero-field-cooled temperature-dependent magnetization, has a metallurgical rather than an electronic nature, and is controlled by the crystal lattice distortion and the microstructure defects. The observed enhancement of the magnetoresistance effect in the LSMO/BTO bilayer at room temperature make this object greatly beneficial in the development of new hybrid ferromagnetic/ferroelectric devices.